Batman : hush - Loeb, Jeph (DC Comics, 2019)
"Gotham City's worst criminals--Joker, Riddler, Ra's al Ghul, Clayface and others--have emerged to throw Batman's life into utter chaos. However, these villains are part of a much more elaborate, sinister scheme to destroy the Dark Knight once and for all, one headed by a mastermind much closer to Bruce Wayne than any foe before. Gotham City is infected by a crime epidemic and all of Batman's enemies have emerged to throw his life into utter chaos, but little do they know that they're all pawns of the villainous Hush in an elaborate game of revenge against Bruce Wayne. Pushed past his breaking point, Batman will need to use more than the world's greatest detective skills to uncover the true identity of this mysterious mastermind before it's too late."--